Benchmark of Nanoparticle Tracking Analysis on Measuring Nanoparticle Sizing and Concentration - MAGUIRE, CIARAN; Sillence, Katherine; Roesslein, Matthias; Hannell, Claire; Suarez, Guillaume; Sauvain, Jean-Jacques; Capracotta, Sonja; Contal, Servane; Cambier, Sebastien; El Yamani, Naouale; Dusinska, Maria; Dybowska, Agnieszka; et al. (My University, 2017)
One of the greatest challenges in the manufacturing and development of nanotechnologies is the requirement for robust, reliable, and accurate characterization data. Presented here are the results of an interlaboratory comparison (ILC) brought about through multiple rounds of engagement with NanoSight Malvern and ten pan-European research facilities. Following refinement of the nanoparticle tracking analysis (NTA) technique, the size and concentration characterization of nanoparticles in liquid suspension was proven to be robust and reproducible for multiple sample types in monomodal, binary, or multimodal mixtures. The limits of measurement were shown to exceed the 30–600 nm range (with all system models), with percentage coefficients of variation (% CV) being calculated as sub 5% for monodisperse samples. Particle size distributions were also improved through the incorporation of the finite track length adjustment (FTLA) algorithm, which most noticeably acts to improve the resolution of multimodal sample mixtures. The addition of a software correction to account for variations between instruments also dramatically increased the accuracy and reproducibility of concentration measurements. When combined, the advances brought about during the interlaboratory comparisons allow for the simultaneous determination of accurate and precise nanoparticle sizing and concentration data in one measurement.
PUBLISHED
Keywords: Iterative learning control; Nanoparticles; Particulate matter; Geometrical size effect; Nanoscience & Materials; Instrumentation, Techniques (Physical Science; NANOPARTICLES; Nanoparticle Tracking Analysis; Scientific Instrumentation; benchmarking